2020
DOI: 10.1097/rct.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapies for Melanoma Brain Metastases: A Primer for Radiologists

Abstract: Objective The purpose of this article is to provide a primer for radiologists outlining the modern systemic therapies used in melanoma brain metastases, including tyrosine kinase inhibitors and immune checkpoint inhibitors. The role of radiologic treatment response evaluation will be discussed from the standpoint of both modern systemic therapies and more traditional treatments. Conclusion Understanding the role of systemic treatments in melanoma brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The median overall survival (OS) of patients with melanoma brain metastases (MBM) has historically been approximately 4 months after diagnosis. Recent studies have shown that immune checkpoint inhibitors targeting the programmed cell death protein 1 (PD1) and cytotoxic Tlymphocyte associated protein 4 (CTLA-4) pathways as well as novel small-molecule tyrosine kinase inhibitors targeting BRAF driver mutations, can improve survival in MBM (2). Margolin et al reported a phase II trial investigating the activity of ipilimumab in MBM patients and showed that it was safe and resulted in tumor regression in some patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…The median overall survival (OS) of patients with melanoma brain metastases (MBM) has historically been approximately 4 months after diagnosis. Recent studies have shown that immune checkpoint inhibitors targeting the programmed cell death protein 1 (PD1) and cytotoxic Tlymphocyte associated protein 4 (CTLA-4) pathways as well as novel small-molecule tyrosine kinase inhibitors targeting BRAF driver mutations, can improve survival in MBM (2). Margolin et al reported a phase II trial investigating the activity of ipilimumab in MBM patients and showed that it was safe and resulted in tumor regression in some patients (3).…”
Section: Introductionmentioning
confidence: 99%